Analisis Strategi Optimalisasi Share Market pada Produk Simpanan Berjangka : Studi Kasus Produk Simpanan Berjangka di KSPPS BMT Fastabiq - Faiqul Hazmi; Rizki Aditiya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
KSPPS BMT Fastabiq has a term savings product. The savings have not been recognized and used by people outside Cepogo Village. The purpose of this study was to determine how the strategy of optimizing market share in term savings products. The method used in this research uses qualitative research methods using data from interviews directly with managers and tellers. data collection techniques used through interviews and observations. The results showed that KSPPS BMT Fastabiq uses several strategies to increase market share in term savings products including promotional strategies (word of mouth, ball pickup and social media), product excellence (uncertain profit sharing system every month and get a deposit note) service strategies (employee services and room facilities) KSPPS BMT Fastabiq has several obstacles in increasing term savings products lack of understanding of the uncertain profit sharing system every month and the lack of marketing department at KSPPS BMT Fastabiq.